Agmatine reduces only peripheral-related behavioral signs, not the central signs, of morphine withdrawal in nNOS deficient transgenic mice - ARICIOĞLU, FEYZA (ELSEVIER IRELAND LTD, 2004)
Agmatine inhibits morphine tolerance/dependence and potentiates morphine analgesia. This study was designed to investigate whether neuronal nitric oxide mediates the actions of agmatine in morphine dependence by using mice lacking a functional form of this enzyme. Mice received agmatine just after the morphine pellet implantation for 3 days twice daily or single injection 30 min before naloxone. In both genotypes treated for 3 days with morphine pellets, naloxone administration precipitated clear signs of withdrawal. Both acute and chronic administration of agmatine reduced withdrawal signs in wild type mice and reduced only peripheral signs of morphine dependence in neuronal nitric oxide synthase knockout mice. Withdrawal signs, that are related to central nervous system activity were not affected. These findings indicate that neuronal nitric oxide synthase partly mediates the effects of agmatine in morphine physical dependence. (C) 2003 Elsevier Ireland Ltd. All rights reserved.
Keywords: agmatine; morphine; dependence; nitric oxide synthase; knockout; CLONIDINE-DISPLACING SUBSTANCE; NEURONAL NO SYNTHASE; RAT-BRAIN; ABSTINENCE SYNDROME; IN-VIVO; TOLERANCE; DEPENDENCE; INHIBITION; ARGININE; RELEASE